2016
DOI: 10.1162/artl_a_00206
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Swarming Behavior Is Shaped by How Predators Attack

Abstract: Animal grouping behaviors have been widely studied due to their implications for understanding social intelligence, collective cognition, and potential applications in engineering, artificial intelligence, and robotics. An important biological aspect of these studies is discerning which selection pressures favor the evolution of grouping behavior. In the past decade, researchers have begun using evolutionary computation to study the evolutionary effects of these selection pressures in predator-prey models. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 61 publications
1
45
0
Order By: Relevance
“…evolved artificial neural networks to show that the presence of a confusable predator might be a sufficient condition for prey individuals to evolve collective behaviour. Using a comparable technique, a similar result was achieved by Olson et al 2122,. who in addition showed that predators may reduce the benefits of prey grouping by attacking peripheral targets and that grouping evolves when the predators attack prey individuals that are located nearby.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…evolved artificial neural networks to show that the presence of a confusable predator might be a sufficient condition for prey individuals to evolve collective behaviour. Using a comparable technique, a similar result was achieved by Olson et al 2122,. who in addition showed that predators may reduce the benefits of prey grouping by attacking peripheral targets and that grouping evolves when the predators attack prey individuals that are located nearby.…”
supporting
confidence: 77%
“…The selfish herd hypothesis suggests that animals form groups in order to reduce their individual domain of danger161718. The confusion effect hypothesis states that a predator attacking a group of visually similar prey might have a hard time tracking and capturing its target141920212223. The many eyes hypothesis suggests that as the size of the group increases the amount of time an individual has to scan the environment decreases2425.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The standard substrate for neuro-evolution are Artificial Neural Networks (ANNs, see e.g., [20]), but we use here a different substrate ("Markov networks" or "Markov Brains") that has proven to be adept at behavioral decision-making tasks [21][22][23][24][25][26][27][28]. In contrast to ANNs in which neurons are continuous-valued and non-firing, neurons in Markov brains (MBs) are digital with only two states: quiescent or firing.…”
Section: Introductionmentioning
confidence: 99%